Analysis of Factors Associated with the Healing Status of Pulmonary Tuberculosis Patients at Puskesmas Perumnas 1 Pontianak in 2018 - Suvianto, Christa Adelia; Hadiyanto (Sriwijaya Journal of Medicine, 2020)
Factors Related to the Healing Status of Patients with Pulmonary Tuberculosis in Puskesmas Perumnas 1 Pontianak2018. Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis that is still a global healthproblem. The healing of patients from TB is important to note because it can harm public health such as providingopportunities for TB disease transmission to family members and the surrounding community, thereby increasing thespread of disease and deaths due to TB. The recovery of TB patients is influenced by several factors such as age, sex, levelof education, knowledge, level of income, access to health services, the role of PMO and treatment compliance. Thisstudy aims to determine the factors associated with the healing status of TB sufferers. This type of research is analyticdescriptive with a cross-sectional design. The instruments used were questionnaires and patient medical records. Datawere obtained by interviewing 106 pulmonary TB patients at their home who had been treated with category 1treatment for 6 months in Perumnas 1 Health Center in Pontianak City. The results of Chi-square test showed that gender(p=0.005), level of education (p=0.002), knowledge (p=0.008), the role of PMO (p=0.001) and medication adherence(p=0.000) are related to the healing status of TB sufferers, while age (p=0.320), income level (p=0.728) and access tohealth services (p=0.141) are not related to the healing status of TB sufferers. Counseling about factors related to TBrecovery is expected to increase the cure rate of TB patients.